Pelaksanaan Fungsi Staffing Kepala Ruang - Herlina Herlina; Luky Dwiantoro; Megah Andriany (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the function of the staffing head of the room in the COVID-19 isolation room. The method used is a qualitative case study. The survey results obtained two main themes: proposing additional staff and carrying out arrangements for variations in team composition, duty schedules, and division of tasks into patient rooms and nurse stations. In conclusion, the head of the room carries out the staffing function in the COVID-19 isolation room, including staff recruitment, scheduling, and assignment of nurses. The charge of the room carries out staff recruitment by proposing additional nurses. The schedule setting is adjusted to the conditions and the number of nurses available, making it easier to arrange a guard schedule. The division of tasks is distinguished between nurses caring for patients and nurses at the nurse station. Keywords: Head of Room, COVID-19 Isolation Room, Staffing